1979
DOI: 10.1111/j.1423-0410.1979.tb04414.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivities of Radioimmunoassay and Enzyme‐Linked Immunosorbent Assay for Detection of Hepatitis B Surface Antigen

Abstract: Radioimmunoassay (RIA) using Austria II (Abbott) was found to be more sensitive for the detection of HBsAg than the Hepanostika Micro-Elisa system (Organon Teknika), by a factor of 5- to 20-fold for subtype 'ad' (with one exception), and 2- to 5-fold for subtype 'ay'. The sensitivities of RIA and the enzyme-linked immunosorbent assay (Elisa) have also been evaluated in the screening of 178 selected serum samples contributed by 7 different laboratories. Of these, 149 were found to be positive for HBsAg by RIA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1980
1980
1989
1989

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In one such study, EIA was found to have a sensitivity comparable with RIA and a false positive rate of 2-2-3.7% which could be reduced to 0.3-1.2% by confirmatory tests for positive sera (Kacaki et al, 1978). In another study, Hepanostika EIA was 2-20 times less sensitive than Ausria I1 RIA and gave a false negative rate of 4% (Hyland et al, 1979). A similar study found comparable sensitivity between the two methods and a false positive rate of 0.48% (Hopkins et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In one such study, EIA was found to have a sensitivity comparable with RIA and a false positive rate of 2-2-3.7% which could be reduced to 0.3-1.2% by confirmatory tests for positive sera (Kacaki et al, 1978). In another study, Hepanostika EIA was 2-20 times less sensitive than Ausria I1 RIA and gave a false negative rate of 4% (Hyland et al, 1979). A similar study found comparable sensitivity between the two methods and a false positive rate of 0.48% (Hopkins et al, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…EIA techniques have been applied successfully to the detection of various antibodies and antigens (Wisdom, 1976) including HBsAg (Wolters et al, 1976;Halbert and Anken, 1977;Wei et al, 1977). EIA kits for HBsAg testing have become available commercially and have been compared with RIA (Hopkins et al, 1978;Kacaki et al, 1978;Hyland et al, 1979;Haas and Hotz, 1980). These studies compared a direct EIA, (Hepanostika@, Organon, Teknika), with RIA (Ausria II@, Abbott Laboratories) in tests with serum panels obtained in Europe and Australia.…”
Section: Introductionmentioning
confidence: 99%
“…Others have also found the Hepanostika to be less sensitive than the RIA [1,2]. The instruc tions of the manufacturer for the calculation of the cutoff values should be clearer.…”
Section: Discussionmentioning
confidence: 99%